The Use of Effective Video Media in Enhancing Knowledge and Attitudes towards Malaria Prevention Among the Elderly - Sulastri Sambo; Tria Astika Endah Permatasari; Lily Herlina (Postgraduate, University of Mataram, 2024)
The number of elderly people worldwide increased by 221 million in 2022. This number is predicted to grow to 994 million in 2030. The elderly are a risk group with an age range of more than 65 years. Elderly age is usually characterized by a decline in bodily and physiological function, which causes the elderly to be less capable of adapting to disease exposures, including malaria. A preliminary study conducted in the Sentral Mimik Health Center's service area found that 13 respondents had low knowledge and attitudes regarding malaria prevention. At the same time, 1 other person showed sufficient knowledge and attitudes regarding malaria prevention in Mimika Regency. Purpose: This research aims to determine the effectiveness of education health using video educational media on the knowledge and attitudes of the elderly in preventing malaria at the Pasar Sentral Mimika Health Center in Mimika Regency. Method: This research employs Quasi Experimental design using Pretest-Posttest with control group design approach. The population in this study was 86 elderly people living in the Pasar Sentral Mimika sub-district. The sample size was 70 people divided into 2 groups, 35 in the intervention group and 35 in the control group, who were taken using simple techniques. Data were analyzed using a Paired t-test and multivariate analysis using the Manova test. Results: The distribution of the knowledge level among the elderly before the intervention was 3.88, and the average value after being given the intervention increased to 8.13. Meanwhile, the average attitude value distribution for elderly attitudes before the intervention was 13.58, and the average value after the intervention increased to 24.83. Conclusion: The average value of the elderly's knowledge level improved after receiving health education using video media in the intervention group at Pasar Sentral Mimika Health Center.